Aerosolized antibiotics in the treatment of hospital-acquired pneumonia/ventilator-associated pneumonia - Yun Jung Jung; Eun Jin Kim; Young Hwa Choi (The Korean Journal of Internal Medicine, 2022)
Aerosolized antibiotics are being increasingly used to treat respiratory infections, especially those caused by drug-resistant pathogens. Their use in the treatment of hospital-acquired pneumonia and ventilator-associated pneumonia in critically ill patients is especially significant. They are also used as an efficient alternative to overcome the issues caused by systemic administration of antibiotics, including the occurrence of drug-resistant strains, drug toxicity, and insufficient drug concentration at the target site. However, the rationale for the use of aerosolized antibiotics is limited owing to their insufficient efficacy and the potential for underestimated risks of developing side effects. Despite the lack of availability of high-quality evidence, the use of aerosolized antibiotics is considered as an attractive alternative treatment approach, especially in patients with multidrug-resistant pathogens. In this review, we have discussed the effectiveness and side effects of aerosolized antibiotics as well as the latest advancements in this field and usage in the Republic of Korea.